Pengaruh Model Discovery Learning Terhadap Hasil Belajar Matematika Siswa Kelas VII SMP - Angga Ardianto; Dodik Mulyono; Sri Handayani (Jurnal Inovasi Matematika, 2019)
The title article is influence model Discovery Learning to learning outcomes Mathematics Students Class VII SMP. This research problem formulation is there influence significant model Discovery Learning to Discovery Learning to learning outcomes mathematics students class VII SMP?. The aim research is to know influence model Discovery Learning to to learning outcomes mathematics students class VII SMP. The research used method is true experimental design by comparing model Discovery Learning with learning conventional. The research population is all over students class VII SMP amount to 263 student, and sampel the research s student class VII.6 and class VII.3 taken by random. Class VII.6 given learning with model Discovery Learning while class VII.3 with learning konvensional. Technik collection data used is Technik tes. The Average value student class used learning model Discovery Learning big as 80,31 while to class learning used learning conventional big as 73,73. The data collected analyzed used uji-t at a significant . Based on the results of calculations uji-t is thit= 2,13 >ttab = 1,671 can concluded that there is significant influence Model Discovery Learning to learning outcomes mathematics student class VII SMP.